Ambient air pollution and cause-specific risk of hospital admission in China: A nationwide time-series study - Gu, Jiangshao; Shi, Ying; Zhu, Yifang; Chen, Ning; Wang, Haibo; Zhang, Zongjiu; Chen, Ting (PLoS medicine, 2020)
[...]the lung autonomic nervous system may be provoked by pulmonary exposure, which could then result in autonomic nervous system imbalance [15]; the levels of stress hormones may also be altered [16]. Ninety-five percent of the total Chinese population was covered by social health insurance schemes by the end of 2017 [21]. [...]hospital admission records can provide reliable and timely information on the health status of a geographically defined population in China. Since January 1, 2013, class 3 hospitals in China have been mandated to automatically submit inpatient discharge records to the HQMS on a daily basis, in a nationally standardized format. All data used were anonymized and de-identified prior to analysis, under the supervision of Bureau of Medical Administration, National Health Commission of the People’s Republic of China. Because the data were analyzed at the aggregate level with no individual identifiers involved, institutional review board approval and participant written consent were not required for this study.